2012
DOI: 10.13057/biofar/f100203
|View full text |Cite
|
Sign up to set email alerts
|

The test of suren (Toona sureni) leaf extract potential as insecticide of grayak caterpillar

Abstract: Noviana E, Sholahuddin, Widadi S. 2012. The test of suren (Toona sureni) leaf extract potential as insecticide of grayak caterpillar (Spodoptera litura) on soybean. Biofarmasi 10: 46-53. Grayak caterpillar (Spodoptera litura F.) is an important pest in the most of food crops (polyphagous). The control of S. litura generally still uses the chemical insecticides that negatively affect the environment and ecosystem. One of the ways of environmentally friendly control was with vegetable insecticides. Suren (Toona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…These indicated that T. sinensis and T. diversifolia more effectively suppressed the aphid attacks on flower organs and reduced petal abnormality that might prevent flower opening. The effectivity of T. sinensis and T. diversifolia as a botanical insecticide was also reported by Kurniawan, Yulani, & Rachmadiarti (2013) to control Plutella xylostella on green mustard, Spodoptera litura on soybean (Noviana et al, 2012), brown planthopper (Nilaparvata lugens) on rice (Subandi, Chaidir, & Nurjanah, 2016) and Callosobruchus maculatus on storage of seeds (Pangihutan et al, 2016).…”
Section: Agronomical and Yield Properties Of Chrysanthemum Treated Plantsmentioning
confidence: 54%
“…These indicated that T. sinensis and T. diversifolia more effectively suppressed the aphid attacks on flower organs and reduced petal abnormality that might prevent flower opening. The effectivity of T. sinensis and T. diversifolia as a botanical insecticide was also reported by Kurniawan, Yulani, & Rachmadiarti (2013) to control Plutella xylostella on green mustard, Spodoptera litura on soybean (Noviana et al, 2012), brown planthopper (Nilaparvata lugens) on rice (Subandi, Chaidir, & Nurjanah, 2016) and Callosobruchus maculatus on storage of seeds (Pangihutan et al, 2016).…”
Section: Agronomical and Yield Properties Of Chrysanthemum Treated Plantsmentioning
confidence: 54%
“…Pertumbuhan larva secara in vitro ditentukan berdasarkan referensi dari Utami (2010). Daya reproduksi dihitung menggunakan rumus Noviana et al (2012).…”
Section: S Frugiperdaunclassified
“…Pemanfaatan daun suren secara tradisional sebenarnya telah dimanfaatkan petani untuk mengusir serangga. Daun suren juga memiliki kandungan bahan aktif seperti surenon, surenin, surenolakton, sedrelon, dan beberapa karotenoid yang diduga merupakan trans-beta karoten, zeasantin, dan laktukasantin, yang memiliki aroma yang tidak disukai hama sehingga dapat dimanfaatkan sebagai repellent (Noviana et al, 2012).…”
Section: Hasil Dan Pembahasan 1 Aplikasi Pestisida Nabati Ekstrak Dau...unclassified